Aspectos Históricos e organizacionais da agricultura familiar no desenvolvimento da região Nova Alta Paulista - Pinto, Leonardo de Barros [UNESP]; Lourenzani, Ana Elisa Bressan Smith [UNESP]; Lourenzani, Wagner Luiz [UNESP]; Mochiuti, Julianna Coracini [UNESP] (My University, 2012)
Nova Alta Paulista region, with strong aptitude for agribusiness, is one of the poorest in the state of São Paulo. However, the development of agribusiness productive chains in the region is very heterogeneous. The study aimed at analyzing how the historical background and organizational arrangements in family farming have contributed to regional development by promoting improvements in social welfare at Nova Alta Paulista region. To this end, we analyzed the case of the Associação Agrícola de Junqueirópolis - AAJ, an organization that has been successful in the search for alternative of agricultural production. Integrated to local and global market, this organization has ensured the maintenance of many farmers and generated positive externalities for the entire region. Thus, this case shows the organizational arrangement based on cooperation can be an alternative for family farmers achieve higher levels of welfare and development.
Family farming historical and organizational aspects of Nova Alta Paulista region
Keywords: Acerola fruit; Cooperation; Family farming; Rural development